Risk Management System in PT. Unilever Indonesia, Tbk - Rizky Amalia Sinulingga (Universitas Airlangga, 2019)
Unilever is a multinational company produced various products which are foods, beverages, cleaning agents and personal care. One most important BoD duty are responsible for identifying and evaluating the company’s exposure to risks, and ensuring that potential risks are effectively mitigated. Effective risk management is fundamental for great business management, and Unilever Indonesia’s success as an organization depends on company ability to identify and exploit the key risks and opportunities for the business. Internal assurance and compliance monitoring are in place to review the strategy risk setting. Internal independent re-assurance (internal audit and corporate audit) and external re-assurance play a key role in ensuring that operational risks and business execution risks are properly addressed and managed. This research aims to describe the Unilever business risk matrix in the recent risk environment and concerned were assigned to manage the risks within their respective streams. The result show, the highest risk that Unilever faced is high competition because competitors have more differentiated products and declining demand for the company product. The mitigation must be implemented to reduce the loss. The company should monitor external market trends and collect feedback from consumer, Implemented research and development function to translate the trends, Regularly update business forecast of business results and cash flows and rebalance investment priorities, and also Flexible business model allows the company to adapt all portfolio and respond to develop new offerings.